Between Relativism and Imperialism: Navigating Moral Diversity in Cross‐Cultural Bioethics. Issue 3 (21st April 2014) - Beck, Daniel
Abstract: The need for explicit theoretical reflection on cross‐cultural bioethics continues to grow as the spread of communication technologies and increased human migration has made interactions between medical professionals and patients from different cultural backgrounds much more common. I claim that this need presents us with the following dilemma. On the one hand, we do not want to operate according to an imperialist ethical framework that denies and silences the legitimacy of cultural values other than our own. On the other hand, we do not want to backslide into a form of cultural relativism that is unable to critically appraise cultural practices that are harmful, unjust, or oppressive. I examine two prominent attempts – the principlism of Tom Beauchamp and James Childress and the Contractarianism of Robert Baker – to frame cross‐cultural bioethics between these two extremes and argue that both approaches have significant flaws. The principlist approach fails to provide a non‐question begging way to identify cross‐cultural norms that does not already assume the universal legitimacy of moral principles dominant in North American society. Baker's contractarianism cannot grapple with the realities of political power imbalances that often characterize cross‐cultural moral disputes. I suggest that a naturalized feminist framework, though not free of its own theoretical difficulties, provides the best alternative for approaching moral diversity respectfully and critically.